Numerical studies of cyclic behavior and design suggestions on triple-truss-confined buckling-restrained braces. (1st September 2017) - Guo, Yan-Lin; Zhou, Peng; Wang, Meng-Zheng; Pi, Yong-Lin; Bradford, Mark Andrew
Highlights: Cyclic behavior and design of a triple-truss-confined buckling-restrained brace (TTC-BRB) is investigated. The TTC-BRB achieves higher external restraining flexural stiffness and overall load-carrying capacity. Equilibrium method is utilized to deduce elastic buckling load of a pin-ended TTC-BRB. Effect of restraining ratio of the TTC-BRB on its cyclic behavior and failure mechanism is explored. Load-carrying capacity of the TTC-BRB under cyclic loading is proportional to restraining ratio. Abstract: The cyclic behavior and design of a triple-truss-confined buckling-restrained brace (TTC-BRB) is investigated, especially when it is used in mega-frame high-rise buildings and long-span spatial structures as a long-span BRB. The TTC-BRB is formed by introducing an additional structural system of rigid truss frames to the outside of a common double-tube BRB in order to achieve a higher external restraining flexural stiffness as well as a high overall load-carrying capacity. An analytical method is utilized to derive a formula of the elastic buckling load of a pin-ended TTC-BRB, which is verified and modified through FE analyses. The effect of restraining ratio of the TTC-BRB on its cyclic behavior and failure mechanism is explored. The findings indicate that the TTC-BRB may have two different failure modes, namely in-plane and out-of-plane instability failures of the chord subjected to compression at the mid-span of the TTC-BRB. In addition, the load-carrying capacity of the TTC-BRB under cyclic loading is found to be proportional to the restraining ratio, and there exists a lower limit of the restraining ratio which ensures the core could reach its full cross-sectional yield load before overall instability failure of the TTC-BRB. Furthermore, in order for the TTC-BRB to be an energy dissipation type of BRBs, the lower limit requirement of the restraining ratio should be satisfied and its end constructional and strength design should be carefully carried out to avoid its premature failure. The investigation of the elastic buckling load and cyclic behavior as well as failure mechanism of the TTC-BRB provides fundamentals to the further development of a comprehensive design method of the TTC-BRB.